Effective and realistic sequestration of Sr2+ and B3+ ions from the aqueous environments using coral reefs based Ca-MCM-41: Gulf of Suez as case study - Sayed, Alshaima; El-Sherbeeny, Ahmed M.; Abdel-Gawad, Gouda Ismail; Mohamed, Essam A.; Al Zoubi, Wail; Abukhadra, Mostafa R. (Frontiers in Chemistry, 2025)
A mesoporous calcium-bearing siliceous framework (Ca-MCM-41) was synthesized using natural coral reef carbonate rocks as precursors. The structural characterization, confirmed through XRD, SEM, FT-IR, and BET analyses, validated the formation of the MCM-41 framework with well-defined mesoporous properties and a high surface area of 159.6 m2/g. The developed Ca-MCM-41 was evaluated as a potential adsorbent for the removal of Sr2+ and B3+ ions from both aqueous solutions and real seawater samples collected from the Gulf of Suez, Egypt. The adsorption capacity at saturation reached 285.9 mg/g for Sr2+ and 86.1 mg/g for B3+, demonstrating the framework’s high affinity for these contaminants. The adsorption mechanisms were elucidated using steric and energetic parameters, as derived from statistical physics-based isotherm models. The Ca-MCM-41 framework exhibited a higher active site density (148.9 mg/g) for Sr2+ compared to B3+ (54.8 mg/g), explaining its superior sequestration performance for strontium ions. Each receptor site was capable of accommodating up to three Sr2+ ions and 2 B3+ ions, indicating a multi-ionic interaction process and preferential vertical alignment during adsorption. Energetic analysis revealed that the sequestration process occurred via physical adsorption with interaction energies below 7 kJ/mol, alongside exothermic and spontaneous behavior, as evidenced by calculated internal energy, entropy, and enthalpy values. The developed Ca-MCM-41 structure demonstrated notable efficiency in real seawater applications, achieving sequestration percentages of 80% for Sr2+ and 64% for B3+, considering their average concentrations (24.2 mg/L for Sr2+ and 12.85 mg/L for B3+) in a 1-L volume. These findings highlight the high potential of Ca-MCM-41 as an effective and sustainable adsorbent for Sr2+ and B3+ removal in environmental water treatment applications.